Estudo de revestimentos obtidos por aspersão térmica de pós de Fe-NbC em tocha de plasma - Rocha, Ricardo César da Silva (2017)
Thermal spraying processes are used to obtain coatings, which can reduce erosion, minimizing the effects of corrosion or for repairing surfaces, with applications in the petroleum, aerospace and electrical industries, among others. NbC carbide has been outstanding in the mechanical, chemical and microelectronic industries since it has properties such as high hardness, high melting point (3610 ° C), high thermal conductivity, high chemical stability, besides resistance to radiation. The properties of the coatings depend on the chemical composition and the microstructure, which are influenced by the process parameters. The technique of deposition through an untransferred arc plasma torch has been studied for coating processing. Fe-NbC is a new product developed to be used as reinforcement because it provides improvement in the mechanical properties of metallic materials. This work presents the results of an investigation on the formation, characterization and tribological performance of hard layers obtained by thermal spraying, using non-transferred arc plasma from Fe-NbC powders deposited on ABNT 1020 steel substrate. To get the layers, the working current and the gas flow of the torch were varied. The obtained coatings were characterized by X-ray diffraction analysis, optical microscopy, scanning electron microscopy, chemical analysis, roughness, Vickers microhardness and pin-to-disk tests. The results indicated that the variations of the deposition parameters have changed the hardness and the coefficient of friction due to the formation of NbC and Fe3O4 phases.